Molecular phylogeny of the subgenus Sophophora of Drosophila derived from large subunit of ribosomal RNA sequences. - Pelandakis, M.; Higgins, D.G.; Solignac, M. (Genetica, 1991)
RNA sequencing has been used to assess the relationships among species of the subgenus Sophophora of the genus Drosophila. Two divergent domains, D1 and D2, of the large ribosomal RNA (28S), totalling 550 nucleotides have been sequenced using the rRNA direct sequencing method. A tree has been reconstructed from the neighbor-joining algorithm and the confidence intervals were evaluated by the bootstrap procedure. Results have shown that the branching of the willistoni and saltans groups of the subgenus Sophophora is very ancient and probably predates that of the subgenus Drosophila. The other groups and subgroups of Sophophora are clustered in three main lineages: 1) the melanogaster and oriental subgroups; 2) the montium subgroup; 3) the ananassae subgroup of the melanogaster group clustered with the fima and obscura groups. Thus, in comparison with our results, several taxa of various ranks appear paraphyletic (the genus Drosophila, the subgenus Sophophora and the melanogaster group). Our biochemical phylogeny is only in partial agreement with the pattern of Throckmorton's radiations as well as with classical taxonomy, both based on morphological data.